KOMPILASI HUKUM ISLAM (KHI) SEBAGAI HASIL IJTIHAD ULAMA INDONESIA - Herawati, Andi (State Institute of Islamic Studies (IAIN) Palu, 2011)
Prior to the emergence of the Compilation of Islamic Law, the Islamic law employed and applied by the Religious Court to resolve disputes, are found in the fiqh books written and complied by Islamic jurists several centuries ago. As a result, the fiqh books employed by the jurists of the Religious Courts are different from one another. The Compilation of Islamic Law contains the rules of Islamic law in accordance with the conditions of the legal requirements and the legal awareness of Indonesian Muslims. The Compilation of Islamic Law is a manifestation and result of application of the existing various sects of fiqh and is equipped with Indonesian scholars’ fatwa in response to the problems that arise so that the the Compilation of Islamic Law can be used as a reference in solving the problem of marriage, inheritance and endowments.